Hi Daniel,

Your approach is a good one! You know that \\(p\leq g(q)\\) and \\(p\leq g'(q)\\) are both equivalent to \\(f(p)\leq q\\), and so they must be equivalent to each other. What relations do you get when you let \\(p=g(q)\\)? When you let \\(p=g'(q)\\)?

Your approach is a good one! You know that \\(p\leq g(q)\\) and \\(p\leq g'(q)\\) are both equivalent to \\(f(p)\leq q\\), and so they must be equivalent to each other. What relations do you get when you let \\(p=g(q)\\)? When you let \\(p=g'(q)\\)?